Painting and Podcasting as Play: Assemblages (With)in Classroom-Situated Multimodal Design. Issue 3 (March 2021) - Rust, Julie
Background: Researchers interested in more playful literacy practices often abandon school-related contexts to instead follow young people to after-school settings, community spaces, social spaces, home environments, and online hangouts. However, play also makes itself visible, even (and sometimes especially) in more formalized learning spaces. Sometimes it emerges subversively in much the same way that flowers grow through cracks in concrete. Other times, teachers deliberately carve out experiences for students to make space for humor, creativity, laughter, and social imagining. Purpose/Objective/Research Question: This inquiry examines two questions: What assemblages of play emerge when youth engage in multimodal composition in classroom spaces? What did these assemblages of play produce? Participants: Participants included youth and teachers from two very different classrooms engaging in a diverse set of multimodal composition projects: one 6th-grade class in an independent school engaging in the creation of podcasts, and one 8th-grade class in a rural public school painting a scene from a recently read novel. Research Design: This inquiry was designed as a qualitative case study. Data Collection: Data sources gathered for this project included descriptive fieldnotes taken during approximately 3 hours of classroom observation during multimodal design, audio recordings during class sessions, photographs taken at the school sites, digital products produced by youth, reflective interviews with teachers, follow-up focus groups with 6th-graders, and reflective surveys filled out by all 8th-grade participants. Findings: Two focal assemblages emerged from various participant/researcher vantage points. Youth conceptualized play as craft, and the researcher observed work-play flows. Conclusions: Recommendations include (a) better recognizing play across age groups and places/spaces, (b) conceptualizing play as a complicated assemblage of materials, humans, emotions, technologies, and space-times, and (c) embracing work-play flows.